1999
DOI: 10.1016/s0028-3932(99)00065-2
|View full text |Cite
|
Sign up to set email alerts
|

Laterality in the perception of temporal cues of musical timbre

Abstract: Laterality in the perception of non-stationary aspects of musical timbre was investigated in 54 right-handed non-musicians. Timbre di erences were produced by altering the amplitude envelope of a steady-state complex tone. Two single-choice tests with attention directed to one ear were usedÐa dichotic test and a monaural test with contralateral white noise. Dependent variables were reaction time and accuracy. Both tests showed a signi®cant left ear advantage for reaction time. For the accuracy variable, a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 31 publications
0
19
1
Order By: Relevance
“…Finally, some studies have suggested a left-ear advantage for tonal stimuli [26], [27], [28]. Though any ear advantage should have been controlled for by the counterbalanced presentation of each tone at the two ears, we analyzed if such an advantage was present in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, some studies have suggested a left-ear advantage for tonal stimuli [26], [27], [28]. Though any ear advantage should have been controlled for by the counterbalanced presentation of each tone at the two ears, we analyzed if such an advantage was present in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, some studies failed to detect ear asymmetries for timbre processing 12‐15. However, left‐ear advantage (LEA), indicative of a right‐hemisphere superiority, was reported in several studies using natural instruments,16‐18 synthetic sounds,19,20 and realistic or unrealistic (played backward) musical instruments 17. All of these laterality studies strongly support a right‐hemisphere priority for timbre perception.…”
Section: Laterality Studiesmentioning
confidence: 96%
“…DL has been broadly used in the study of hemispherical asymmetries and the main result that it yielded is that, in general, subjects with left‐hemispheric language lateralization are faster and more accurate in reporting verbal items presented at the right ear (Kimura, 1961; Studdert‐Kennedy & Shankweiler, 1970). Conversely, they exhibit a left ear advantage for tasks involving the recognition of musical or environmental sounds (Kallman & Corballis, 1975; Boucher & Bryden, 1997; Brancucci & San Martini, 1999, 2003).…”
Section: Introductionmentioning
confidence: 99%